Technological and Environmental Evaluation of Incinerator Systems for Sustainable Waste-to-Energy Solutions in Denpasar City - Putu Aryastana; I Putu Manik Kurniawan; I Gusti Agung Putu Eryani; Gde Wikan Pradnya Dana; Jackson Chang Hian Wui (CV. Literasi Indonesia, 2025)
The rapid urbanization and tourism growth in Denpasar City, Bali, have led to increasing waste management challenges. Currently, only 22% of the daily 850 tons of waste is managed at the source, with the rest transported to landfills. This study aims to evaluate the implementation of Waste-to-Energy (WES) incineration systems as a potential solution to both waste disposal and energy production. The research uses a quantitative method involving primary data collection through interviews and secondary data from existing documentation. Three incinerator designs were analyzed based on parameters like energy efficiency, emissions, and environmental impact. The results show that the third incinerator system delivers the highest power output at 445.67 KW, although it also produces moderate pollutant emissions. The second design system, however, strikes a better balance, offering both lower emissions and effective power generation, making it the most environmentally favorable option. The study contributes to the growing body of research on WES technology, highlighting the need for advanced design optimization to minimize environmental impacts while maximizing energy output.